2013
DOI: 10.1124/jpet.113.203620
|View full text |Cite
|
Sign up to set email alerts
|

HCN1 Channels as Targets for Anesthetic and Nonanesthetic Propofol Analogs in the Amelioration of Mechanical and Thermal Hyperalgesia in a Mouse Model of Neuropathic Pain

Abstract: Chronic pain after peripheral nerve injury is associated with afferent hyperexcitability and upregulation of hyperpolarizationactivated, cyclic nucleotide-regulated (HCN)-mediated I H pacemaker currents in sensory neurons. HCN channels thus constitute an attractive target for treating chronic pain. HCN channels are ubiquitously expressed; analgesics targeting HCN1-rich cells in the peripheral nervous system must spare the cardiac pacemaker current (carried mostly by HCN2 and HCN4) and the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 63 publications
1
65
0
Order By: Relevance
“…Previous work from our group suggested that phosphorylation and inhibition of GlyR α3 contributes to inflammatory but not to neuropathic hyperalgesia (36), while others have shown that 2,6-DTBP still alleviated neuropathic hyperalgesia (37). We therefore investigated whether the antihyperalgesic effects of 2,6-DTBP in neuropathic pain also depended on GlyR α3.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous work from our group suggested that phosphorylation and inhibition of GlyR α3 contributes to inflammatory but not to neuropathic hyperalgesia (36), while others have shown that 2,6-DTBP still alleviated neuropathic hyperalgesia (37). We therefore investigated whether the antihyperalgesic effects of 2,6-DTBP in neuropathic pain also depended on GlyR α3.…”
Section: Resultsmentioning
confidence: 89%
“…Does modulation of GlyRs contribute to analgesic actions of 2,6-DTBP? 2,6-DTBP not only potentiates GlyRs but also inhibits hyperpolarization and HCN ion channels (37), in particular HCN1 channels, which are expressed in peripheral nociceptors and contribute to pain sensitization (39). In addition, antioxidant properties of 2,6-DTBP (40, 41) may directly or indirectly (e.g., via inhibition of the T-type Ca 2+ channel, ref.…”
Section: Resultsmentioning
confidence: 99%
“…Propofol also has anti-inflammatory and anti-oxidant properties which may contribute to analgesia. Besides, propofol can selectively inhibit hyperpolarisation-activated cyclic nucleotide-regulated 1 (HCN1) channels, by which it provides an anti-hyperalgesic effect on chronic pain caused by peripheral nerve injury [34,35]. Another putative mechanism through which propofol may exert its analgesic properties is through desensitisation of transient receptor potential cation channel, subfamily A, member 1 (TRPA1), a receptor involved in the sensation of pain, cold and itch [36].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al have observed that increased expression of HCN1 and HCN2 and a shift in the activation curve of Ih occur in a rat model of neuropathic pain (Du et al 2013a, b). The activity of HCN1 is repressed by analgesics, while knockout of HCN2 abolishes neuropathic pain in response to nerve injury in mice (Emery et al 2011;Emery et al 2012;Tibbs et al 2013). Xie et al observed increased Ih in primary afferent neurons of rats with nerve CCI-induced spontaneous pain (Xie et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased expression of HCN1 and HCN2 and a shift in the activation curve of Ih have been reported to occur in a rat model of neuropathic pain (Du et al 2013a, b), while HCN2 knockout mice have been found to show no neuropathic pain, in response to thermal or mechanical stimuli, after a nerve lesion (Emery et al 2011). Furthermore, pharmacologic inhibition of Ih in peripheral nociceptive neurons has been observed to reduce mechanical allodynia and thermal hyperalgesia in animal models of neuropathic pain (Du et al 2013a;Tibbs et al 2013;Young et al 2014), alleviate inflammation-induced hypersensitivity of the rat temporomandibular joint (Hatch et al 2013), and augment activity-dependent conduction velocity slowing in axotomized C-fibers (Mazo et al 2013). Thus, there is substantial evidence that enhanced HCN channel function may contribute to neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%